1986
DOI: 10.1007/bf02412119
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ethyl (R,S)-nipecotate on the behaviors of highly and minimally aggressive female golden hamsters

Abstract: The GABA uptake inhibitor ethyl (R,S)-nipecotate produces a dose-dependent suppression of aggression in highly aggressive hamsters but not in minimally aggressive ones. This suppression occurs at doses below those producing peripheral cholinergic effects; at the highest dose used it persists after these effects have dissipated. Doses sufficient to suppress aggression have no significant effect on grooming, locomotor activity and other behaviors but do affect sunflower seed acceptance. The differential effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…It seems likely that these membrane actions require the formation of metabolites of progesterone that are capable of binding to a subunit of the GABA A receptor [Baulieu, 1997]. Potegal's [1986] work with highly aggressive female hamsters showed that when GABA uptake was blocked pharmacologically, aggression decreased. GABA binding in the brains of aggressive female hamsters was shown to be significantly higher than in nonaggressive females [Potegal et al, 1982], and steroids can modulate GABA receptor binding in hamster brains [Canonaco et al, 1989a,b].…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that these membrane actions require the formation of metabolites of progesterone that are capable of binding to a subunit of the GABA A receptor [Baulieu, 1997]. Potegal's [1986] work with highly aggressive female hamsters showed that when GABA uptake was blocked pharmacologically, aggression decreased. GABA binding in the brains of aggressive female hamsters was shown to be significantly higher than in nonaggressive females [Potegal et al, 1982], and steroids can modulate GABA receptor binding in hamster brains [Canonaco et al, 1989a,b].…”
Section: Discussionmentioning
confidence: 99%
“…In general, drugs that inhibit depolarization at the GABA receptor decrease aggression (Davanzo and Sydow 1979;Haug et al 1980;Rodgers and DePaulis 1982;Simler et al 1983;Potegal 1986;Ferreira et al 2000;Podhorna and Krsiak 2000). The BZ full, partial, and inverse agonists, clobazam, diazepam, zolpidem, zopiclone, 3-carboethoxy-β-carboline, and bentazepam decrease offensive aggression in encounters between male mice (Krsiak 1975;Skolnick et al 1985;Martin-Lopez and Navarro 1998).…”
Section: Introductionmentioning
confidence: 94%
“…Whether the newer anticonvulsants will have similar efficacy is not established. Since animal studies have shown inverse ␥-aminobutyric acid (GABA)ergic modulation of aggression, it would be presumed that GABAergic agents would be effective in treating aggression (27,28). The authors present two cases wherein the addition of adjunctive tiagabine, a novel GABA uptake inhibitor, was effective in seizure management and in reduction of behavioral abnormalities.…”
Section: Introductionmentioning
confidence: 97%